Parents' and Guardians' Perception of Play as an Expression of Children's Mental Health (PRÁXIS EM SAÚDE, 2025)
This study aims to understand, from the psychoanalytic theory perspective, the importance of play as an expression of children’s mental health. It seeks to investigate parents’ perceptions regarding children’s expression of feelings through play activities, thus allowing an observation of how much parents believe in the relevance of this form of expression in child language. To obtain these data, a literature review was conducted on the works of Freud and Winnicott. Additionally, a public opinion questionnaire was applied using Google Forms, with structured questions on the mentioned topic. Subsequently, for data analysis, graphs generated on the Forms platform were used. The results showed that the majority of the surveyed sample perceives the importance of play for children. However, there remains a percentage of parents and guardians who do not fully understand the role of this activity in the development of children’s psychic processes.
Keywords: Play; Development; Expression; Parents; Mental health